Biovalorization and induction parameters optimization for a neutral cellulase isolated and characterized from Bacillus Licheniformis KM999221 (Funded Work) - SARASWATI GUPTA,; VARSHA KELKAR-MANE, (International Journal of Pharma and Bio Sciences, 2019)
Agricultural and industrial wastes are among the causes of environmental pollution. Biovalorization has been a promising alternative in treating and converting agricultural residues into commercially valuable and industrial products. This study focuses on the induction and characterization of neutral cellulase from Bacillus licheniformis KM999221 isolated from an archival document and optimization of parameters for valorization of rice husk. Microbial deterioration of archives by bacterial growth is a worldwide problem. Many bacterial genera usually found on the archival materials have the ability to deteriorate and degrade the cellulose chains in the archives. On the other archives could be a good source for the isolation of cellulose degrading bacteria. The purified enzyme monomer with molecular weight of about 30 KDa and was characterized using SDS–PAGE and MALDI-TOF/TOF-MS. Optimum activity of purified cellulase was found at 37°C and 43% of original activity as retained up to 70°C Enzyme optimally hydrolysed near neutral pH (pH 7.0) and enzyme enhanced upon addition of Ca+2 and Mn+2 at 10mM concentration and Fe+2 at 5mm concentration respectively. Yeast extract and peptone (w/v) proved to be the best nitrogen sources for the production of cellulase. When induced with fine powdered rice husk the production of enzyme reached 2200 U/mg in 72 hours of incubation. The study unfolded the implications of particle size on induction as well as substrate utilization optimizing valorization strategies for rice husk. Biovalorization is the process of reusing, recycling or composting waste materials and converting them into more useful products including materials, chemicals, fuels or other sources of energy.